The Predictability of Using Selfie and Self –image Editing Behaviors in Body Dysmorphic Disorder among Yarmouk University Students - Momani, Fawwaz Ayoub; Al-Amri, Mu'aathah Shehadah (Jordan Journal of Social Sciences, 2024)
The study aimed at finding out the level of selfie-use, self-image editing behavior, and body dysmorphic disorder among Yarmouk University students. Further, it aimed at examiningthe predictability of of selfie use, and self-portrait editing behavior in body dysmorphic disorder (BDD). To achieve the objectives of the study, the researcher developed measures of selfie use, tendency to edit photos, and body dysmorphic disorder. The study sample consisted of (1720) male and female students from Yarmouk University in Jordan distributed to (519) male students and (1201) female students. The findings of the study revealed that the level of using selfies and the tendency to edit pictures among students was moderate. Further, the findings showed that the prevalence of body dysmorphic disorder among sample of the study was (20.3%). Moreover, the results revealed that the mood modification dimension of the scale of selfie use has a predictive ability of body dysmorphic. It was found out that the gender variable had a predictive ability of body dysmorphic disorder in favor of male students. The results revealed that the dimensions of self-editing behavior scale (psychological emotions, attitude towards self-editing) had a predictive ability of dysmorphic disorder. Finally, the study findings showed that there was no predictive ability for each dimension (prominence, self-esteem, seeking attention, social norms, and demographic variables i.e., major, school year, place of residence, GPA) of the dysmorphic disorder.